Bioremediation of Chlorpyrifos Contaminated Soil Using Biomass of Fruit-vegetable Waste - V, Jina Sruthi; P, Asha (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
India is a country where more than 70% of its population relies on its agricultural production. Excess production of crops leads to contamination by pests and to prevent these pesticides are in wide use. Chlorpyrifos is a pesticide commonly used due to its broad-spectrum activity. It is highly toxic and does not get degraded easily leading to irreversible hazards to the environment. The process of bioremediation involves the all-encompassing action of microbes, including aerobic and anaerobic bacteria and fungi. Most of the earlier studies involved the direct use of microbes or their enzymes in the bioremediation processes. In the present study we have attempted bioremediation of soil samples harnessed with chlorpyrifos at two different concentrations (10% & 20%) using crude fruit-vegetable waste biomass. The results of the study proved an exemplary reduction in the COD values as well as an enhancement in the essential nutrients (N,P,K) in the soil. Chlorpyrifos was completely degraded into its intermediary compounds phosphorothioic acid and1-methyl dodecyl benzene within a span of 30 days.